Experiences of working at a construction project site in Cape Town as a foreigner to South Africa - Kengue Tchaptchet, Peggy Njamen (Cape Peninsula University of Technology, 2019)
Thesis (MTech (Business Administration in Project Management))--Cape Peninsula University of Cape Town, 2018. === The demand for project management specialists grows worldwide. Traditionally, certain industries have been more project-oriented than others. However, nowadays, organisations in both private and public sector have embraced Project Management as the ideal means of managing projects with the hopes of ensuring the intended benefit delivery. Project management is a skill that is in high demand in South Africa. Project managers play a vital role in the economic growth of a developing country. This has resulted in organisations investing considerable resources to ensure that they build the capacity needed to effectively manage projects. South Africa is a diverse country in terms of age, culture, education, gender, race and religion amongst a group of people living or working together. Globalization has increased diversity within the workplace which is challenging and worsened knowing the country’s history. The attributes required to be a successful project manager include excellent interpersonal, communication skills, project management skills, adept problem solving and the ability to work well under pressure, whilst being highly adaptable and logical thinker. Confidence, strong negotiating skills and being able to motivate a team in order to achieve the goals is necessary; a project manager is a leader and a skilled delegator. Managers have diverse team to manage which speaks to the need for people of the different social dispositions to be able to co-exist. In the workplace, there is generally an organisational culture that speaks largely to how things are done. The culture observed by the outside world is largely because of the coming together of all the different people, with different origins, different tastes and different objectives. In this study, a construct was developed to identify the perceptions of the subordinates about the environment they work in and to identify the exact differences – things or behaviours that are perceived to be alien to their expectations.